Vortex valve - Adámek Karel; Kolář Jan; Peukert Pavel (EPJ Web of Conferences, 2018)
The paper deals with a flow field inside the so-called vortex valve, used as an outlet device on retention reservoirs for retention of rainstorms and later slow outflow into sewerage etc. The system is very simple, without moving parts. Using the method of numerical flow simulation, the unusual flow characteristic Δp = f(Q), containing two branches, is explained. Further, there it is studied influence of both inlet/outlet opening sizes on the form of the characteristic. Results can be used for designing the new model series of valves for various flows.